The Effect of the On-Boarding Program and Organizational Culture on Employee Performance - Inriyani, Nadia; Haedar, H.; Hasbi, Andi Rizkiyah (Golden Ratio of Human Resource Management, 2026)
This study examines the influence of the onboarding program and organizational culture on the performance of employees at Bumi Mineral South Sulawesi. A quantitative research approach was employed, with data collected through questionnaires. The population consisted of 525 employees, and the sample was determined using a simple random sampling technique with the Slovin formula, resulting in 84 respondents. Data were analyzed using multiple linear regression with the SPSS software. The findings indicate that the onboarding program positively and significantly affects employee performance. Similarly, organizational culture also shows a positive and significant influence on performance. Furthermore, when considered simultaneously, the onboarding program and organizational culture significantly enhance employee performance. These results highlight the importance of structured onboarding and a supportive organizational culture in shaping employee performance outcomes. Accordingly, it is recommended that the management of Bumi Mineral South Sulawesi continue to strengthen these two dimensions as strategic priorities to sustain and improve employee performance.